NILAI EKONOMI ANAK, MOTIVASI, DAN SELF-ESTEEM PEKERJA ANAK - Rizkianto, Robi; Muflikhati, Istiqlaliyah; Hernawati, Neti (Jurnal Ilmu Keluarga dan Konsumen, 2013)
Analysis of influence of the child’s economic value and motivation on self-esteem of child labor in one of the business center in Bogor District was the goal of this research. The study involved 40 child laborers and their parents that were selected by snowball. Data were analyzed using independent samples t-test and multiple linear regression test. The results showed that parents’ perceptions of child labor related future of child’s economic value and the child’s economic value currently in the moderate category. Motivation of child labors (intrinsic and extrinsic) and self-esteem were also in the moderate category. Self-esteem of child labor increased by increasing length of child to attend formal education and decreased in children who was dropping outs of school. Selfesteem of child labor was also decreased with decreasing extrinsic motivation.